Sequential assembly of cell-laden hydrogel constructs to engineer vascular-like microchannels - Du, Yanan; Ghodousi, Majid; Qi, Hao; Haas, Nikhil; Xiao, Wenqian; Khademhosseini, Ali (Biotechnology and bioengineering, 2011)
Microscale technologies, such as microfluidic systems, provide powerful tools for building biomimetic vascular‐like structures for tissue engineering or in vitro tissue models. Recently, modular approaches have emerged as attractive approaches in tissue engineering to achieve precisely controlled architectures by using microengineered components. Here, we sequentially assembled microengineered hydrogels (microgels) into hydrogel constructs with an embedded network of microchannels. Arrays of microgels with predefined internal microchannels were fabricated by photolithography and assembled into 3D tubular construct with multi‐level interconnected lumens. In the current setting, the sequential assembly of microgels occurred in a biphasic reactor and was initiated by swiping a needle to generate physical forces and fluidic shear. We optimized the conditions for assembly and successfully perfused fluids through the interconnected constructs. The sequential assembly process does not significantly influence cell viability within the microgels indicating its promise as a biofabrication method. Finally, in an attempt to build a biomimetic 3D vasculature, we incorporated endothelial cells and smooth muscle cells into an assembled construct with a concentric microgel design. The sequential assembly is simple, rapid, cost‐effective, and could be used for fabricating tissue constructs with biomimetic vasculature and other complex architectures. Biotechnol. Bioeng. 2011; 108:1693–1703. © 2011 Wiley Periodicals, Inc.